(untitled) (Baghdad Science Journal, 2007)
Blood samples were collected from chemotherapy-treated and -untreated patients with acute lymphoblastic leukemia (ALL). Samples were analyzed for the serum levels of total sialic acid (TSA), C3, and C4, as well as TSA levels in the white blood cells (WBCs) homogenate. In the group of untreated patients, TSA levels in the sera and WBCs were significantly increased as compared to normal subjects. A similar significant increase was observed in the levels of serum C3 and C4. In the group of treated patients, TSA levels in the sera and WBCs were significantly reduced, while insignificant decreases were observed in the serum levels of C3 and C4 as compared to the untreated patients. Correlation analysis showed weak relationships between TSA and complement levels in the sera of normal subjects, untreated, or treated patients. Thus, these results suggest that, despite the apparently similar behavior of the levels of TSA and the complement proteins before and after chemotherapy, TSA can not be used as an indicator to monitor the levels of complement proteins in response to chemotherapy.